Antifungal activity of natural products indicated by herb sellers (raizeiros) for the treatment of oral candidiasis - Vanessa Maria Freire Abílio; Bruno da Silva Mesquita; Evelyn Darly da Silva; Fabíola Vilar de Queiroz Carvalho; Luciana Lucena Aranha de Macêdo; Ricardo Dias de Castro (Revista Cubana de Estomatología, 2014)
An increasing resistance of Candida yeasts to the synthetic antifungals currently available has driven the search for new plant-derived antifungal compounds. In this respect, the present study aimed to evaluate the in vitro antifungal activity of decoctions from Schinus terebinthifolius Raddi (Brazilian pepper tree), Cinnamomum zeylanicum Breym (cinnamon) and Punica granatum Linn (pomegranate) against three species of Candida genus (C. albicans, C. tropicalis and C. krusei). Such plant material was sold by herb sellers in three distinct street fairs (A, B and C). The test to determine the products antifungal activity was performed in triplicate by means of the diffusion method on solid medium, in which sterile filter paper discs were soaked in 50 µL of the extracts and then placed on culture medium. Data were assessed by measuring the diameters of halos of fungal growth inhibition, in millimeters (mm), and it was considered the mode of the values found. Antifungal activity of S. terebinthifolius Raddi and C. zeylanicum Breym was observed against C. krusei, but were identified differences among the products obtained in different locations. Punica granatum Linn decoction presented antifungal activity on the three yeasts under study. Also, were found differences among the products acquired in the street fairs, but only the samples of Punica granatum Linn from fair A were able to inhibit fungal growth of all yeasts analyzed. Thus, it is concluded that all the products assessed showed antifungal activity, but differences were found depending on the location where these were obtained and on the sensitivity to the strains assayed.